Pharmaceutical analysis and drug interaction studies : African potato (Hypoxis hemerocallidea) - Purushothaman Nair, Vipin Devi Prasad (Rhodes University, Faculty of Pharmacy, Pharmacy, 2006)
In order for a medicinal product to produce a consistent and reliable therapeutic response, it is essential that the final composition of the product is invariable and that the active ingredient/s is/are present in appropriate, non-toxic amounts. However, due to the complexity involved in the standardization of natural products, quality control (QC) criteria and procedures for the registration and market approval of such products are conspicuously absent in most countries around the world. African Potato (AP) is of great medical interest and this particular plant has gained tremendous popularity following the endorsement by the South African Minister of Health as a remedy for HIV/ AIDS patients. Very little information has appeared in the literature to describe methods for the quantitative analysis of hypoxoside, an important component in AP. It has also been claimed that sterols and sterolins present in AP are responsible for its medicinal property but is yet to be proven scientifically. To-date, no QC methods have been reported for the simultaneous quantitative analysis of the combination, Î²- sitosterol (BSS)/ stigmasterol (STG)/ stigmastanol (STN), purported to be present in preparations containing AP. The effect of concomitant administration of AP and other herbal medicines on the safety and efficacy of conventional medicines has not yet been fully determined. Amongst the objectives of this study was to develop and validate quantitative analytical methods that are suitable for the assay and quality control of plant material, extracts and commercial formulations containing AP. Hypoxoside was isolated from AP and characterized for use as a reference standard for the quality control of AP products and a stability-indicating HPLC/ UV assay method for the quantitative determination of hypoxoside was developed. In addition, a quantitative capillary zone electrophoretic (CZE) method was developed to determine hypoxoside, specifically for its advantages over HPLC. A HPLC method was also developed and validated for the quantitative analysis of BSS, STG and STN in commercially available oral dosage forms containing AP material or extracts thereof. The antioxidant activity of an aqueous extract of lyophilized corms of AP along with hypoxoside and rooperol were investigated. In comparison with the AP extracts and also with hypoxoside, rooperol showed significant antioxidant activity. The capacity of AP, (extracts, formulations, hypoxoside and rooperol as well as sterols to inhibit in vitro metabolism of drug substrates by human cytochrome P450 (CYP) enzymes such as CYP 3A4, 3A5 and CYP19 were investigated. Samples were also assessed for their effect on drug transport proteins such as P-glycoprotein (P-gp). Various extracts of AP, AP formulations, stigmasterol and the norlignans, in particular the aglycone rooperol, exhibited inhibitory effects on CYP 3A4, 3A5 and CYP19 mediated metabolism.These results suggest that concurrent therapy with AP and other medicines, in particular antiretroviral drugs, can have important implications for safety and efficacy. Large discrepancies in marker content between AP products were found. Dissolution testing of AP products was investigated as a QC tool and the results also revealed inconsistencies between different AP products.
Keywords: Potatoes -- Africa; Potatoes -- Therapeutic use; AIDS (Disease) -- Treatment; HIV infections -- Drug therapy; Medicinal plants